Analyses of Hungarian sour cherry germplasm with simple sequence repeat markers - Z. György; T. Szabó; J. Nyéki; A. Pedryc (International Journal of Horticultural Science, 2010)
Twenty-four sour cherry cultivars (genotypes), belonging to four cultivar groups were fingerprinted using microsatellite markers. All genotypes have been arisen from the Carpathian basin, which could be secondary gene centre of sour cherry, since its progenitor species, ground cherry and sweet cherry overlap here. Five SSR primer pairs, earlier used for fingerprinting Turkish sour cherry germplasm were tested. None of the five primer pairs showed any polymorphism within the cultivar groups. The primer pairs were able to distinguish between the cultivar groups. The Oblacsinszka and the Cigánymeggy cultivar groups were the most difficult to separate, while the Pándy cultivar group was the most distinguishable.